Pengaruh Gaya Hidup, Kualitas Produk, dan Citra Merek terhadap Keputusan Pembelian Produk Skincare G2 Glow di Kota Batam - Manao, Santi Agustina; Hikmah, Hikmah (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine how lifestyle, product quality, and brand perception influence customer decisions in Batam City to purchase G2Glow skin care products. A total of 204 respondents who had used G2Glow products were selected from the customer base using purposive sampling. In addition to testing data quality, impact, traditional assumptions, and hypotheses, the data obtained were analyzed using multiple linear regression. The results of the linear regression study show that lifestyle, product quality, and brand image have a positive and significant influence on purchasing decisions Together, these three factors can explain purchasing decisions. The T-test and F-test show that customer decisions in Batam City to purchase G2Glow skin care products are favorably and significantly influenced by lifestyle, product quality, and brand image, both separately and together. This study offers in-depth information about product marketing tactics in the cosmetics sector to help businesses understand and improve the factors that influence consumer choices. A more successful marketing approach can be used to increase product competitiveness in the market by considering lifestyle, product quality, and brand image.